2022
DOI: 10.1021/acs.molpharmaceut.2c00052
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of the Reduced Solubility of the Pirfenidone–Fumaric Acid Cocrystal in Sustaining the Release Rate from Its Tablet Dosage Form by Conducting Comparative Bioavailability Study in Healthy Human Volunteers

Abstract: Pirfenidone (PFD) is the first pharmacological agent approved by the US Food and Drug Administration (FDA) in 2014 for the treatment of idiopathic pulmonary fibrosis (IPF). The recommended daily dosage of PFD in patients with IPF is very high (2403 mg/day) and must be mitigated through additives. In the present work, sustained-release (SR) formulations of the PFD-FA cocrystal of two different strengths such as 200 and 600 mg were prepared and its comparative bioavailability in healthy human volunteers was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…The comparative diffusion studies of SMX and SMX–PIP were carried out using the modified Franz diffusion apparatus by a dialysis membrane-70 ( M w : 14,000 Da, Himedia) . The dialysis membrane separated the donor and acceptor compartments with a diffusion area of 1.13 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparative diffusion studies of SMX and SMX–PIP were carried out using the modified Franz diffusion apparatus by a dialysis membrane-70 ( M w : 14,000 Da, Himedia) . The dialysis membrane separated the donor and acceptor compartments with a diffusion area of 1.13 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The comparative diffusion studies of SMX and SMX−PIP were carried out using the modified Franz diffusion apparatus by a dialysis membrane-70 (M w : 14,000 Da, Himedia). 35 The dialysis membrane separated the donor and acceptor compartments with a diffusion area of 1.13 cm 2 . To obtain preliminary in vitro comparative data of the materials, the studies were conducted in buffer media (pH 6.8), which mimics the intestinal pH.…”
Section: Morphological Analysis 2341 Field Emission Scanning Electron...mentioning
confidence: 99%
“…Also, it is to be noted that some cocrystals do not undergo complete dissociation or solution-mediated phase transformation in solubility/dissolution studies . However, it was observed that these cocrystals transform into individual components upon going into systemic circulation from the oral route of administration . Thus, using a cocrystal as a ligand to be docked in the binding pocket as a substrate/inhibitor of any receptor defeats the underlying purpose, as these cocrystals are not supposed to manifest any pharmacological action different from the API itself.…”
Section: An Outlook On the Applicability Of Molecular Docking Studies...mentioning
confidence: 99%
“…16 The recommended daily dosage of PFD is also high (2403 mg), which will cause severe side effects. 16,17 A sustained-release formulation is believed to be able to maintain plasma concentration over a longer duration of time, thereby increasing bioavailability and reducing dosage (or dosing frequency) and dose related side effects. [16][17][18][19] Recently, two cocrystals of PFD with fumaric acid and trimesic acid were reported by A. Ghosh.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 A sustained-release formulation is believed to be able to maintain plasma concentration over a longer duration of time, thereby increasing bioavailability and reducing dosage (or dosing frequency) and dose related side effects. [16][17][18][19] Recently, two cocrystals of PFD with fumaric acid and trimesic acid were reported by A. Ghosh. 18 These forms exhibit drastically reduced solubility and dissolution rates, and have the potential to be developed as sustained release formulations.…”
Section: Introductionmentioning
confidence: 99%